Relationship between insurance and access and cost of care in patients with diabetes before and after the affordable care act. Issue 1 (16th December 2020) - Varadarajan, Arjun; Walker, Rebekah J.; Williams, Joni S.; Bishu, Kinfe; Nagavally, Sneha; Egede, Leonard E.
Abstract : Purpose: The purpose of this paper is to examine the influence of insurance coverage changes over time for patients with diabetes on expenditures and access to care before and after the Affordable Care Act (ACA). Design/methodology/approach: The Medical Expenditure Panel Survey (MEPS) from 2002–2017 was used. Access included having a usual source of care, having delay in care or having delay in obtaining prescription medicine. Expenditures included inpatient, outpatient, office-based, prescription and emergency costs. Panels were broken into four time categories: 2002–2005 (pre-ACA), 2006–2009 (pre-ACA), 2010–2013 (post-ACA) and 2014–2017 (post-ACA). Logistic models for access and two-part regression models for cost were used to understand differences by insurance type over time. Findings: Type of insurance changed significantly over time, with an increase for public insurance from 30.7% in 2002–2005 to 36.5% in 2014–2017 and a decrease in private insurance from 62.4% in 2002–2005 to 58.2% in 2014–2017. Compared to those with private insurance, those who were uninsured had lower inpatient ($2, 147 less), outpatient ($431 less), office-based ($1, 555 less), prescription ($1, 869 less) and emergency cost ($92 less). Uninsured were also more likely to have delay in getting medical care (OR = 2.22; 95% CI 1.86, 3.06) and prescription medicine (OR = 1.85; 95% CI 1.53, 2.24) compared with privately insured groups. Originality/value: Though insurance coverage among patients with diabetes did not increase significantly, the type of insurance changed overtime and fewer individuals reported having a usual source of care. Uninsured individuals spent less across all cost types and were more likely to report delay in care despite the passage of the ACA.